EXPLORING THE CONJUNCTION OF CHILDHOOD AND RITUALS: AN ANALYTICAL STUDY OF KUTHIYOTTAM BASED ON SELECT TEMPLES IN KERALA - K. Nair, Asha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Kerala has a rich repertoire of folk arts and forms. The diverse culture of the place gives expression to these forms. Kuthiyottam is a ritualistic offering unique to the Devi temples of Kerala. It is a mélange of physical and religious facets. Though the performance has its basis on human sacrifice, it entails a perfect synchronization of song and dance movements. Despite exhibiting certain common traits, the practice varies markedly across various regions. The study primarily focuses on the Kuthiyottam performance prevalent in Pulimath Devi Temple in Thiruvananthapuram, while also examining the regional variations at Attukal and Chettikulangara temples. Kummi and Kavithavum are distinct segments of Kuthiyottam songs. The songs are predominantly focused on the veneration of the deity but also encompass characters from the epic. Boys aged eight to twelve are chosen for the ritual. Accompanied by percussion, children are led in front of the deity and the ritual of ‘chooralkuthu’, piercing by cane is done on the flanks of the children. The paper intents to explore the conjunction of childhood and rituals concerning the performing folk art, Kuthiyottam.